MENAKAR KESUKSESAN PEGAWAI OUTSOURCING DI SEKTOR IRIGASI - Wahyuni, Desak Made; Darma, Gede Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
This research aims to examine more deeply the influence of the management of outsourcing manpower management aspects controlling (supervision of work) on the performance of outsourced personnel of the Balai Wilayah Sungai Bali - Penida in irrigation. The sample used is the total population of 146 outsourced workers in Bali. Data was collected through Google Form and analyzed through the Structural Equation Model (SEM) approach with Smart PLS 3.2.9 software. This study has proven that the better the management of outsourcing personnel in controlling aspects, the better the performance of outsourced workers in the irrigation work sector. The contribution given from the results of this study is theoretically able to add to the literature in the field of human resource management, especially related to the outsourcing workforce performance. Practically, this research will be very useful for companies providing outsourcing to be able to optimize the performance of outsourced employees with good management